Comparison of urine neutrophil gelatinase-associated lipocalin to serum creatinine to assess kidney function in neonatal asphyxia - Winston Leonardo Tanzil; Rocky Wilar; Max Frans Josef Mantik; Adrian Umboh; Suryadi Nicolaas Napoleon Tatura (Indonesian Pediatric Society, 2016)
Background Infants with neonatal asphyxia have multiorgan damage, such as to the kidneys (50%), central nervous system (28%), cardiovascular system (25%), and lungs (23%). Neonatal asphyxia reduces kidney perfusion, often leading to acute kidney injury (AKI) after asphyxia. Neutrophil gelatinase-associated lipocalin (NGAL) levels in the blood, urine and kidney tissue increased rapidly in AKI. Urinary NGAL is proposed to have better performance in diagnosing AKI than creatinine due to its earlier, rapid level increase and it is less invasive.Objective To compare urinary NGAL to serum creatinine as a marker to assess kidney function in neonatal asphyxia.Methods Diagnostic comparison study with cross-sectional design was performed at neonatal intensive care unit (NICU) of Prof. Dr. R. D. Kandou Hospital, Manado from November 2015 to February 2016. All subjects had neonatal asphyxia. Data were analyzed using descriptive analysis, receiver-operator characteristic (ROC) curve, and Z-test.Results Urinary NGAL with cut-off point of 652.24 ng/mL can predict AKI in neonates with asphyxia with 100% sensitivity, 75% specificity, 52.3% positive predictive value, and 100% negative predictive value. Chi-square test resulted in a value of x2 = 20.036, P=0.0001).This shows that urinary NGAL levels >652,24 ng/mL can predicts AKI by 20 times in infants with neonatal asphyxia. So, urinary NGAL performs better than serum creatinine, therefore it can replace serum creatinine as an alternative non-invasive diagnostic test for diagnosing AKI in infants with neonatal asphyxia.Conclusion The diagnostic value of urinary NGAL is higher than that of serum creatinine in assessing kidney function in neonatal asphyxia.Â